Legal Protection for Children in Cases of Online Sexual Abuse: A Comparative Study - Rahayu, Sri; Monalisa, Monalisa; Monita, Yulia; Sugiharto, Melyana (Jambe Law Journal, 2022)
The advancement of technology has provided numerous benefits to society. However, they also proved to yield negative consequences, such as the increase in criminal activities, including online sexual offenses against children which adversely impact children around the world. Legal regulations in Indonesia are still not optimal and require improvements in order to provide better protection for children in Indonesia. In response to the high level of violence against children in Indonesia, President Joko Widodo issued the Presidential Regulation regarding the national strategy for the elimination of violence against children on July 15, 2022, which includes the provision of the policy, regulatory implementation, and law enforcement. To support the elimination of sexual violence against minors, this study seeks to provide ideas and concepts for improving Indonesia's criminal law. Employing a descriptive research design and a comparative legal research method, with the assistance of literature studies, the researchers drew comparisons of legal regulations and policies addressed to eradicate online sexual offenses against children between Indonesia, the United Kingdom, the Philippines, and Ghana. Based on the findings, this study formulates seven ways to improve legal protection for children against online sexual offenses in Indonesia through repressive and preventive means